Neuroprotective Effect of AM404 Against NMDA-Induced Hippocampal Excitotoxicity - Saliba, Soraya Wilke; Bonifacino, Tiziana; Serchov, Tsvetan; Bonanno, Giambattista; de Oliveira, Antônio Carlos Pinheiro; Fiebich, Bernd L. (Frontiers in Cellular Neuroscience, 2019)
Different studies have demonstrated that inflammation and alterations in glutamate neurotransmission are two events contributing to the pathophysiology of neurodegenerative or neurological disorders. There are evidences that N-arachidonoylphenolamine (AM404), a paracetamol metabolite, modulates inflammation and exerts neuroprotective effects on Huntington’s and Parkinson’s diseases, and ischemia. However, the effects of AM404 on the production of inflammatory mediators and excitotoxicity in brain tissue stimulated with N-methyl-D-aspartic acid (NMDA) are not elucidated. In this present study, we investigated the effects of AM404 on the production of inflammatory mediators and neuronal cell death induced by NMDA in organotypic hippocampal slices cultures (OHSC) using qPCR, Western blot, and immunohistochemistry. Moreover, to comprehend the mechanism of excitotoxicity, we evaluated the effects of AM404 on glutamate release in hippocampal synaptosomes and the NMDA-induced calcium responses in acute hippocampal slices. Our results showed that AM404 led to a significant decrease of cell death induced by NMDA, through a mechanism possibly involving the reduction of glutamate release and the calcium ions responses. Furthermore, it decreased the expression of the interleukin (IL)-1β. This study provides new significant insights about the anti-inflammatory and neuroprotection effects of AM404 on NMDA-induced excitotoxicity. To understand the effects of AM404 in these processes might contribute to the therapeutic potential of AM404 in diseases with involvement of neuroinflammation and neurodegeneration and might lead to a possible future treatment of neurodegenerative diseases.